2006
DOI: 10.1016/j.ydbio.2006.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Basis of lethality in C. elegans lacking CUP-5, the Mucolipidosis Type IV orthologue

Abstract: Mutations in MCOLN1, which encodes the protein h-mucolipin-1, result in the lysosomal storage disease Mucolipidosis Type IV. Studies on CUP-5, the human orthologue of h-mucolipin-1 in Caenorhabditis elegans, have shown that these proteins are required for lysosome biogenesis. We show here that the lethality in cup-5 mutant worms is due to two defects, starvation of embryonic cells and general developmental defects. Starvation leads to apoptosis through a CED-3-mediated pathway. We also show that providing worm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 37 publications
6
61
0
5
Order By: Relevance
“…RNAi was done by the feeding method as previously described (Timmons and Fire, 1998). Markers used were: pgp-2(gk114) I (Nunes et al, 2005); cup-5(ar465) III (Fares and Greenwald, 2001b); cup-5(zu223) III (Hersh et al, 2002);unc-36(e251) III (closely linked to cup-5) (Brenner, 1974;Fares and Greenwald, 2001a;Fares and Greenwald, 2001b);unc-69(e587) III (Brenner, 1974); ced-9(n1950n2161) III (Gumienny et al, 1999); rme-2((b1008) IV (Grant and Hirsh, 1999); cpl-1(ok360) V (Britton and Murray, 2004); rme-1(b1045) V (Grant et al, 2001); cup-10(ar479) V (Dang et al, 2003); rme-6(b1018) X (Sato et al, 2005); bIs1 pRF4] (which expresses a fusion of the worm YP170 protein VIT-2 to GFP) (Grant and Hirsh, 1999);cdIs77[GFP::LGG-1;unc-119(+)-pmyo-2::GFP] X (which expresses GFP-LGG-1 in all cells and GFP in the pharynx) (Schaheen et al, 2006);nT1[qIs51] IV, V (is a dominant balancer) (Siegfried et al, 2004); and qC1 (a balancer chromosome that suppresses recombination between cup-5 and unc-36) (Graham and Kimble, 1993). cup-5(zu223) unc-36(e251) worms bearing various transgenes were isolated from qC1-balanced parent heterozygotes; the eggs from these homozygous progeny were analyzed in the various assays.…”
Section: Elegans Strains and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…RNAi was done by the feeding method as previously described (Timmons and Fire, 1998). Markers used were: pgp-2(gk114) I (Nunes et al, 2005); cup-5(ar465) III (Fares and Greenwald, 2001b); cup-5(zu223) III (Hersh et al, 2002);unc-36(e251) III (closely linked to cup-5) (Brenner, 1974;Fares and Greenwald, 2001a;Fares and Greenwald, 2001b);unc-69(e587) III (Brenner, 1974); ced-9(n1950n2161) III (Gumienny et al, 1999); rme-2((b1008) IV (Grant and Hirsh, 1999); cpl-1(ok360) V (Britton and Murray, 2004); rme-1(b1045) V (Grant et al, 2001); cup-10(ar479) V (Dang et al, 2003); rme-6(b1018) X (Sato et al, 2005); bIs1 pRF4] (which expresses a fusion of the worm YP170 protein VIT-2 to GFP) (Grant and Hirsh, 1999);cdIs77[GFP::LGG-1;unc-119(+)-pmyo-2::GFP] X (which expresses GFP-LGG-1 in all cells and GFP in the pharynx) (Schaheen et al, 2006);nT1[qIs51] IV, V (is a dominant balancer) (Siegfried et al, 2004); and qC1 (a balancer chromosome that suppresses recombination between cup-5 and unc-36) (Graham and Kimble, 1993). cup-5(zu223) unc-36(e251) worms bearing various transgenes were isolated from qC1-balanced parent heterozygotes; the eggs from these homozygous progeny were analyzed in the various assays.…”
Section: Elegans Strains and Methodsmentioning
confidence: 99%
“…We used quantitative fluorescence measurements instead of western blots for this analysis because the defect in cup-5(zu223) embryos is confined to specific stages of embryonic development (Schaheen et al, 2006). We also focused on developing intestinal cells at these embryonic stages because we can unambiguously identify intestinal (and pharyngeal) cells in cup-5(zu223) embryos based on position and morphology in the embryos.…”
Section: Mrp-4(cd8) Rescues the Lysosomal Degradation Defects Of Cup-mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on CUP-5, the Caenorhabditis elegans ortholog of MCOLN1, have shown that this protein is involved in endocytic processes and lysosome biogenesis and function (Fares and Greenwald, 2001;Schaheen et al, 2006). Interestingly, the endocytosis defect observed in cup-5 mutants could be rescued by the transgenic expression of human MCOLN1 or MCOLN3 (Treusch et al, 2004).…”
Section: +mentioning
confidence: 99%